Meta-analysis of the Impact of Bariatric Surgery on Circulating TMAO Levels as a Predictor of Cardiovascular Disease Risk - Jamialahmadi, Tannaz; Simental-Mendia, Luis E.; Zengin, Gokhan; Almahmeed, Wael; Kesharwani, Prashant; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2024)
Introduction: Trimethylamine N-oxide (TMAO) is a metabolite of the gut microbiota that is considered a cardiovascular risk factor. Because bariatric surgery (BS) produces changes in the composition of the gut microbiota, the production of TMAO can be compromised. Thus, the purpose of this meta-analysis was to determine the effect of BS on circulating TMAO levels. Methods: A systematic search was carried on in Embase, PubMed, Web of Science, and Scopus databases. The meta-analysis was conducted using Comprehensive Meta-Analysis (CMA) V2 software. The overall effect size was determined by a random-effects metaanalysis and the leave-one-out approach. Results: Random-effects meta-analysis of 5 studies consisting of 142 subjects demonstrated a significant increase in circulating TMAO levels after BS (SMD: 1.190, 95% CI: 0.521, 1.858, p<0.001; I2:89.30%). Conclusion: Considering that levels of TMAO are affected after BS due to gut microbial metabolism alteration, there has been a significant elevation in TMAO concentrations observed to occur after BS in obese subjects.
Keywords: microbiome